Pancreatic Metastasis of High-Grade Papillary Serous Ovarian Carcinoma Mimicking Primary Pancreas Cancer: A Case Report - Yusuf Gunay; Ebru Demiralay; Alp Demirag (Case Reports in Medicine)
Introduction. Reports of epithelial ovarian carcinomas metastatic to the pancreas are very rare. We herein present a metastasis of high grade papillary serous ovarian cancer to mid portion of pancreas. Case. A 42-year-old patient was admitted with a non-specified malignant cystic lesion in midportion of pancreas. She had a history of surgical treatment for papillary serous ovarian adenocarcinoma. A cystic lesion was revealed by an abdominal computerized tomography (CT) performed in her follow up . It was considered as primary mid portion of pancreatic cancer and a distal pancreatectomy was performed. The final pathology showed high-grade papillary serous adenocarcinoma morphologically similar to the previously diagnosed ovarian cancer. Discussion. Metastatic pancreatic cancers should be considered in patients who present with a solitary pancreatic mass and had a previous non-pancreatic malignancy. Differential diagnosis of primary pancreatic neoplasm from metastatic malignancy may be very difficult. A biopsy for tissue confirmation is required to differentiate primary and secondary pancreatic tumors. Although, the value of surgical resection is poorly documented, resection may be considered in selected patients. Conclusion. Pancreatic metastasis of ovarian papillary serous adenocarcinoma has to be kept in mind when a patient with pancreatic mass has a history of ovarian malignancy.